Dynamic interconversion and phototransformation processes of protochlorophyllide complexes during greening - Kósa, Annamária; Böddi, Béla (Acta Biologica Szegediensis, 2005)
Photoreduction and interconversion processes of different protochlorophyllide complexes were studied in epicotyl segments of dark-germinated pea (Pisum sativum L.) seedlings illuminated with low-intensity white or 632.8 nm laser light. Analyses of 77 K fluorescence emission spectra showed the direct phototransformation of the monomer, 636 nm emitting complex. The 629 nm emitting complex containing also monomer pigment, regenerated all longer wavelength, flash-photoactive complexes. A dynamic transformation of the protochlorophyllide complexes was also detected during the illumination and/or the subsequent dark-incubation. On the basis of these results, the protochlorophyllide phototransformation schemes can be completed with new pathways.